New Mechanistic Insights into the Ru‐Catalyzed Asymmetric Hydrogenation of β‐Ketoesters. Issue 22 (8th June 2022) - Püntener, Kurt; Bigler, Raphael; Stier, Kenta; Checinski, Marek P.
Abstract: We describe the results of our quantum mechanical investigation of the asymmetric hydrogenation of β‐ketoesters catalyzed by [RuCl2 (MeOH)2 (( R )‐MeOBIPHEP)] (7 a ), which is generated in situ from [Ru(OAc)2 (( R )‐MeOBIPHEP)] (4 a ) and HCl in methanol. Interestingly, HCl not only acts as an activator for 4 a as it has a dramatic effect on the reaction itself: While HCl/4 a =2 leads to rather poor results (36 % ee and 13 % conv. after 4 h at at a substrate‐to‐catalyst ratio (S/C)=50'000), HCl/4 a =20 results in high efficiency (>99.9 % conv.) and enantioselectivity (99 % ee favoring the opposite enantiomer) under otherwise identical conditions. The origin for this sweeping change in performance has remained a mystery for two decades. Here, we show for the first time that a highly selective HCl pathway becomes operational under acidic conditions, which outcompetes moderately selective pathways dominating under neutral conditions. Furthermore, we explain the effects of common phosphorus substituents on the activity of the catalyst. Abstract : New reaction pathways for the asymmetric hydrogenation of β‐ketoesters with [RuCl2 (MeOH)2 (( R )‐MeOBIPHEP)] have been discovered through quantum mechanical investigations. Furthermore, we applied our mechanistic findings to several catalyst derivatives to explain the experimentally observed activity and selectivity.